2015
DOI: 10.1038/onc.2015.124
|View full text |Cite|
|
Sign up to set email alerts
|

Brg-1 targeting of novel miR550a-5p/RNF43/Wnt signaling axis regulates colorectal cancer metastasis

Abstract: Metastasis is one of the main causes of death in patients with colorectal cancer (CRC). Brg-1 is a central component of the SWItch/Sucrose NonFermentable chromatin-remodeling complex, which features a bromodomain and helicase/ATPase activity. The gene encoding Brg-1 is frequently mutated or silenced in human cancers. Several reports have proposed Brg-1 as a tumor suppressor; however, little is known about its role in oncogenesis and metastasis. Here we demonstrated that decreased Brg-1 regulates a novel miR-55… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
49
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 41 publications
6
49
0
1
Order By: Relevance
“…In our previous study, we reported that BRG1 expression is related with lymph node metastases [13]. To further confirm this finding, we measured the expression levels of BRG1 in lymph node metastases and primary tumors from 180 patients with lymph node metastatic CRC by immunohistonchemistry, after which we rated the amount of BRG1 staining by using an immunoreactive score (IRS) (Figure 1A and 1B).…”
Section: Resultsmentioning
confidence: 58%
See 2 more Smart Citations
“…In our previous study, we reported that BRG1 expression is related with lymph node metastases [13]. To further confirm this finding, we measured the expression levels of BRG1 in lymph node metastases and primary tumors from 180 patients with lymph node metastatic CRC by immunohistonchemistry, after which we rated the amount of BRG1 staining by using an immunoreactive score (IRS) (Figure 1A and 1B).…”
Section: Resultsmentioning
confidence: 58%
“…In addition, BRG1 has been shown to interact with the tumor suppressor, p53, thereby leading to the transcriptional activation of target genes, including tumor suppressors such as prohibitin, TopBP1 and HIC1 [2022]. In our previous study, we have shown that mutant or loss functional BRG1 promoted colon cancer metastasis in vitro and in vivo [13]. In this study, we investigated the function of BRG1 in cancer-related lymphangiogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our quest revealed that ring finger 43 (RNF43) is an experimentally verified target of miR-550a-5p in colorectal cancer cells. (96) Interestingly, RNF43 was found to negatively regulate Wnt/bcatenin, (97) which in turn is known to inhibit osteoclastogenesis. (98) Further studies are necessary to elucidate whether this miR-550a-5p/RNF43/WNT pathway is also active in bone.…”
Section: Discussionmentioning
confidence: 99%
“…Among these pathways, Wnt/β-catenin signaling is known to play a major role in the promotion of CRC metastasis [43] and correlates with poor clinical prognosis [44]. Hu et al found that several factors, such as stromal cell-derived factors, can induce the Wnt/β-catenin pathway to promote CRC progression [45], whereas Wang et al showed that Brg-1 can inhibit the Wnt/β-catenin pathway to suppress CRC metastasis [46]. Moreover, nuclear β-catenin accumulation, another important feature of Wnt/β-catenin signaling activation, has frequently been observed in primary CRC tissues [40], which further highlights the essential role of Wnt/β-catenin in the process of metastasis.…”
Section: Discussionmentioning
confidence: 99%